Transformasi Karakter di Layar: Pembelajaran Make-up Prostetik Sederhana untuk Mahasiswa Film - Pramesti, Winda; Owie, Anggra Agastyassa (CV. Ulil Albab Corp, 2025)
Film is a work of art formed by two elements, namely audio elements and visual elements. One element that does not get much attention but actually plays a big role is make-up. Make-up itself is the art of applying makeup or changing the original shape of the face with the help of cosmetic tools and materials. This study uses a qualitative method. Researchers conducted direct interviews with research subjects. Interviews were conducted with students at the Yogyakarta Film Academy and Makeup Lecturers. Researchers conducted direct observations of film make-up learning strategies. Three main methods are used to study prosthetic make-up in films: lectures, Q&A, and practice